Sosialisasi Teknologi Lunas Baja Bagi Pengrajin Kapal Kayu di Kecamatan Galesong Kabupaten Takalar - Lukman Bochary; Mohammad Rizal Firmansyah; Suandar Baso; Farianto Fachruddin; Mansyur Hasbullah; Rosmani Rosmani; Andi Dian Eka Angriani; Muhammad Akbar Aziz; Ganding Sitepu; Misliah Misliah; Abdul Haris Djalante (Faculty of Engineering UNHAS, 2022)
As the main material, wood is required in the process of wooden ships building. The required wood must be water resistant especially for the construction of the ship wooden plank as well as wood in intact form for use on the keel of the ship to support the ship frames. It is increasingly difficult to obtain the required wood for the keel construction need since the requirements for the integrity of the keel construction which must continue throughout the ship. This condition threatens the sustainability of the wooden ship construction process in Indonesia. Hence, material alternative is urgently required for wood substitution for the ship keel. A study has been conducted with a recommendation of a steel keel (dimensions and shape of the keel) as a substitute for a wooden keel for certain ship dimensions. Socialization of this new technology needs to be done to wooden ship craftsmen in South Sulawesi in particular. The partners chosen in this activity were the member of the wooden boat craftsman group